Artificial immune system based optimization technique for voltage profile improvement using unified power flow controller / Nur Dianah Mohd Radzi - Mohd Radzi, Nur Dianah (2007)
This thesis presents the application of Artifial Immune System (AIS) as one of the biological Computing optimization technique with the use of Unified Power Flow Controller (UPFC) for voltage profile improvement.